Aktualisasi Nilai-Nilai Keagamaan saat Menghadapi Pandemi Covid-19 - Ace Somantri; Erwan Komara; Nurlaela Hamidah (LPPM Institut Nasional Laa Roiba Bogor, 2022)
The environment in its various forms, both of physical and in the form of situation, can change humans to be good or vice versa. The environment can also be a stimulant for humans to do something they think is good. With the Covid-19 pandemic, the environment around humans is in a state filled with anxiety. There are at least two main causes: 1) news of death that he hears all the time and 2) uncertainty about the end of this pandemic. Coupled with the government's policies for Work from Home (WfH) and Large-Scale Social Restrictions. it makes the community even more burdened. This research method and approach uses a descriptive qualitative approach and is expected to provide an overview of student religious behavior in dealing with the Covid-19 pandemic. In addition, the type of research is qualitative. Approach research used is a cross sectional studies approach, because this research is carried out at a certain time. Data collection techniques are generally carried out through the submission of a series of questions (questionaries) after which interviews (interviews) will be conducted to several respondents, both structured and unstructured. Presentation of data and submission of reports is done through descriptive method The level of confidence in students' faith in the Covid-19 period when in online learning activities (WFH) showed a very high value reaching a percentage of 99.7%, a high level of confidence increased Muslim students' trust in Allah SWT. In the face of covid-19, Muslim students to be more calm in doing dhikr to Allah SWT reached 70.9% and to actualize Islamic religious values, the majority of students made donations to those affected by covid-19 reaching 33.95% - 68.4%, this is the condition of students Muslims in dealing with Covid-19 psychologically prioritize religious spiritual values. Keyword : Actualization of Religious Values, Islamic Behavior of Students, Overcoming the Covid-19